2014
DOI: 10.1080/09546553.2013.796935
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Boosting Conflict? A Micro-Level Test of the Linkage Between Substance Use and Violence

Abstract: Many studies have emphasized the role of natural resources in the onset and duration of armed conflict. Due to its characteristics, narcotics are considered to be one of the most influential resources. However, the dynamics of how this particular commodity is linked to conflict is still not well understood. Most scholars have focused on the revenue aspects of narcotics and only few have mentioned the micro-level aspect, i.e. the effect of drugs intake and alcohol consumption on combatant's behavior during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…With regard to victim-offender populations, this result may be interpreted in accordance with Hecker and Haer (2015), who suggest that drugs may be consumed in order to feel more vigilant, powerful and fearless (Goldstein et al, 1989) when committing violent acts such as murder or rape, rather than to cope with the psychological impact of PTSD symptoms (Bonin, Norton, Asmundson, Dicurzio, & Pidlubney, 2000). However, we found a significant relationship between PTSD and appetitive aggression, and we hypothesize that comorbid PTSD symptoms, such as revenge fantasies (Maercker & Horn, 2013), may evolve into a proactive intrinsic motivation for violence, i.e.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…With regard to victim-offender populations, this result may be interpreted in accordance with Hecker and Haer (2015), who suggest that drugs may be consumed in order to feel more vigilant, powerful and fearless (Goldstein et al, 1989) when committing violent acts such as murder or rape, rather than to cope with the psychological impact of PTSD symptoms (Bonin, Norton, Asmundson, Dicurzio, & Pidlubney, 2000). However, we found a significant relationship between PTSD and appetitive aggression, and we hypothesize that comorbid PTSD symptoms, such as revenge fantasies (Maercker & Horn, 2013), may evolve into a proactive intrinsic motivation for violence, i.e.…”
Section: Discussionsupporting
confidence: 55%
“…This correlation holds true for South Africa: Between 1999 and 2000, in Cape Town, Johannesburg and Durban, almost 50% of individuals arrested on charges related to family violence, homicide or rape were reported to have been either drunk or under the influence of drugs at the time of the offense (Parry, Plüddemann, et al, 2004). The severity of the committed crimes is positively associated with alcohol or drug consumption preceding the violent act (Chermack and Blow, 2002, Hecker and Haer, 2015, White et al, 2002). Although these data reveal that substance abuse represents a frequent precursor to aggressive behavior (Taylor & Chermack, 1993), the question of whether drug abuse functions as a catalyst (Ching, Daffern, & Thomas, 2012) or in a causal role, remains a controversial issue (Klostermann & Fals-Stewart, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might turn children into fierce fighters who could be even deadlier than adult combatants. Similarly, children are more likely to perpetrate a more diverse set of violent actions, for example, sexual violence, massacres, physical assault or mutilations (Hecker and Haer, 2015). Psychological research also emphasizes that child soldiers show more aggressiveness than adult combatants as they perceive violence as something positive and fascinating (Schauer and Elbert, 2010; Wessels, 2006).…”
Section: Child Soldiers and Rebel Groups’ Fighting Capacities: Theoretical Argumentsmentioning
confidence: 99%
“…Finally, from a political sciences point of view, use of alcohol and drugs can be linked to violence during conflicts. Some studies have shown that after controlling for armed-group-and individual-level variables, drug intake and alcohol consumption boosts the number of violent actions perpetrated during conflicts (10).…”
Section: Links Between Humanitarian Situations and Substance Usementioning
confidence: 99%